Removal of Phenol and o-Cresol by Adsorption onto Activated Carbon - A. Edwin Vasu (E-Journal of Chemistry)
A commercial activated carbon was utilized for the adsorptive removal of phenol and o-cresol from dilute aqueous solutions. Batch mode adsorption studies were performed by varying parameters such as concentration of phenol solution, time, pH and temperature. The well known Freundlich, Langmuir and Redlich-Peterson isotherm equations were applied for the equilibrium adsorption data and the various isotherm parameters were evaluated. The Langmuir monolayer adsorption capacities were found to be 0.7877 and 0.5936 mmole/g, respectively, for phenol and o-cresol. Kinetic studies performed indicate that the sorption processes can be better represented by the pseudo-second order kinetics. The processes were found to be endothermic and the thermodynamic parameters were evaluated. Desorption studies performed indicate that the sorbed phenol molecules can be desorbed with dil. HCl.